Stainless steel material for solid oxide fuel cell and method for manufacturing the same, component for solid oxide fuel cell and solid oxide fuel cell
By controlling the chemical composition and manufacturing process of stainless steel, stainless steel with excellent conductivity and thermal shock resistance at a temperature below 600°C was prepared, which solved the problem of insufficient conductivity and thermal shock resistance of low-temperature working solid oxide fuel cells.
Patent Information
- Application Number
- CN202180071487.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-01-14
- Filing Date
- 2021-12-08
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2041-12-08
AI Technical Summary
The existing solid oxide fuel cells have insufficient conductivity and thermal shock resistance at temperatures below 600°C, making it difficult to meet the needs of low-temperature working fuel cells.
By controlling the chemical composition of stainless steel, including C, Si, Mn, P, S, Cr, Mo, N, Al, Nb, Ti, Ni, Cu and other elements, and using hot rolling and cold rolling manufacturing methods, stainless steel with a high purity index less than 1.50%.
It has achieved stainless steel for solid oxide fuel cells with excellent conductivity and thermal shock resistance at a temperature below 600°C, and is suitable for components of low-temperature working fuel cells.
Smart Images

Figure CN116490631B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a stainless steel material for a solid oxide fuel cell and a method for producing the same, as well as a member for a solid oxide fuel cell and a solid oxide fuel cell. Background Art
[0002] Conventional solid oxide fuel cells (SOFCs) are high-temperature operating types with an operating temperature exceeding 600° C. However, in recent years, low-temperature operating solid oxide fuel cells operating in a temperature range below 600° C. have been proposed (e.g., Patent Documents 1 and 2). Stainless steel is generally used for the components of such solid oxide fuel cells from the perspectives of cost, corrosion resistance, etc.
[0003] Solid oxide fuel cells have been developed mainly as stationary power sources, but in recent years, their use has been expected to expand to various mobile bodies such as business and industrial vehicles, automobiles, and airplanes.
[0004] Prior Art Literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2020-53388
[0007] Patent Document 2: Japanese Patent No. 6696992 Summary of the invention
[0008] The components constituting a solid oxide fuel cell (e.g., separators, interconnectors, current collectors, etc.) are required to have electrical conductivity. However, since the electrical conductivity of the components decreases as the operating temperature decreases, the electrical conductivity of the components used in conventional high-temperature operating solid oxide fuel cells is sometimes insufficient.
[0009] In addition, when the use is expanded to mobile bodies, since the start and stop are more frequent than in stationary types, strong thermal shock resistance is required. However, the components used in conventional stationary solid oxide fuel cells cannot be said to have sufficient thermal shock resistance.
[0010] The present invention is made to solve the above-mentioned problems, and its purpose is to provide a stainless steel material for solid oxide fuel cells having excellent electrical conductivity and thermal shock resistance at a temperature of 600°C or less, and a method for manufacturing the same. In addition, the present invention also aims to provide a solid oxide fuel cell component and a solid oxide fuel cell having the stainless steel material for solid oxide fuel cells having such characteristics.
[0011] The present inventors have conducted intensive studies on stainless steel materials and have found that the above-mentioned problems can be solved by controlling the composition to a specific one, thereby completing the present invention.
[0012] That is, the present invention is a stainless steel material for a solid oxide fuel cell, which contains, by mass, C: 0.030% or less, Si: 1.00% or less, Mn: 1.00% or less, P: 0.050% or less, S: 0.0030% or less, Cr: 13.0% or more and less than 22.0%, Mo: 1.50% or less, N: 0.030% or less, Al: 0.30% or less, Nb: 0.40% or less, Ti: 0.40% or less, Ni: 1.00% or less, and Cu: 1.00% or less, and has a high purity index represented by the following formula (1) of less than 1.50%, and the balance contains Fe and impurities.
[0013] High purity index = 10(C+N)+15S+8P+2(Ti+Nb)…(1)
[0014] In the formula, each element symbol represents the content of each element.
[0015] In addition, the present invention is a method for manufacturing a stainless steel material for a solid oxide fuel cell, wherein a slab is hot rolled and then cold rolled, wherein the slab contains, by mass, C: less than 0.030%, Si: less than 1.00%, Mn: less than 1.00%, P: less than 0.050%, S: less than 0.0030%, Cr: more than 13.0% and less than 22.0%, Mo: less than 1.50%, N: less than 0.030%, Al: less than 0.30%, Nb: less than 0.40%, Ti: less than 0.40%, Ni: less than 1.00%, and Cu: less than 1.00%, and the high purity index represented by the following formula (1) is less than 1.50%, and the balance contains Fe and impurities.
[0016] High purity index = 10(C+N)+15S+8P+2(Ti+Nb)…(1)
[0017] In the formula, each element symbol represents the content of each element.
[0018] Furthermore, the present invention is a member for a solid oxide fuel cell, comprising the above-mentioned stainless steel material for a solid oxide fuel cell.
[0019] Furthermore, the present invention is a solid oxide fuel cell comprising the above-mentioned solid oxide fuel cell member.
[0020] According to the present invention, a stainless steel material for a solid oxide fuel cell having excellent electrical conductivity and heat shock resistance at a temperature below 600° C. and a method for manufacturing the same can be provided. In addition, according to the present invention, a solid oxide fuel cell component and a solid oxide fuel cell having the stainless steel material for a solid oxide fuel cell having such characteristics can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a schematic plan view of a test piece for measuring conductivity. DETAILED DESCRIPTION
[0022] The embodiments of the present invention are described in detail below. The present invention is not limited to the following embodiments, and it should be understood that within the scope of the present invention, based on the common knowledge of those skilled in the art, the following embodiments may be appropriately modified, improved, etc. and the like, and the solutions obtained are also within the scope of the present invention.
[0023] In addition, in this specification, "%" about a component means mass % unless otherwise specified.
[0024] The stainless steel material for solid oxide fuel cells according to an embodiment of the present invention (hereinafter referred to as "stainless steel material") has the following composition: C: 0.030% or less, Si: 1.00% or less, Mn: 1.00% or less, P: 0.050% or less, S: 0.0030% or less, Cr: 13.0% or more and less than 22.0%, Mo: 1.50% or less, N: 0.030% or less, Al: 0.30% or less, Nb: 0.40% or less, Ti: 0.40% or less, Ni: 1.00% or less, Cu: 1.00% or less, a high purity index of less than 1.50%, and the balance containing Fe and impurities.
[0025] Here, the so-called "impurities" are components (such as unavoidable impurities) mixed in due to various factors such as raw materials such as ores and scraps and manufacturing processes when stainless steel materials are industrially manufactured, and refer to components that are allowed within the range that does not adversely affect the present invention. In addition, the so-called "stainless steel material" is a concept including various shapes such as stainless steel strips, stainless steel plates, and stainless steel foils.
[0026] In addition, the stainless steel material according to the embodiment of the present invention may further contain one or more selected from B: 0.0050% or less, Sn: 0.5% or less, V: 0.5% or less, W: 0.5% or less, Ca: 0.010% or less, Mg: 0.010% or less, Zr: 0.50% or less, Co: 0.5% or less, Ga: 0.01% or less, Hf: 0.10% or less, and REM: 0.10% or less, as needed.
[0027] <C: 0.030% or less>
[0028] C is an element that affects the electrical conductivity of stainless steel at temperatures below 600°C. If the C content is too high, the electrical conductivity decreases. Therefore, the C content is set to 0.030% or less, preferably 0.020% or less, and more preferably 0.015% or less. On the other hand, the lower limit of the C content is not particularly limited, but the lower the C content, the more time the refining process takes, and the manufacturing cost may increase. Therefore, the C content is preferably 0.0002% or more, and more preferably 0.0005% or more.
[0029] <Si: 1.00% or less>
[0030] Si is an element that improves the heat resistance of stainless steel and is effective for the formation of Cr oxide film at temperatures below 600°C. However, if the Si content is too much, a continuous oxide of SiO2 is generated at the interface of the stainless steel, thereby reducing the conductivity, and the toughness may be reduced due to hardening. Therefore, the Si content is set to 1.00% or less, preferably 0.80% or less, more preferably 0.60% or less, and further preferably 0.30% or less. On the other hand, the lower limit of the Si content is not particularly limited. From the viewpoint of obtaining the above-mentioned effects brought about by Si, the Si content is preferably 0.05% or more, and more preferably 0.08% or more.
[0031] <Mn: 1.00% or less>
[0032] Mn is an element that improves the toughness of stainless steel and is effective in improving the conductivity of the oxide film by forming (Mn, Cr)3O4 type oxides. However, if the Mn content is too high, the heat resistance and workability may be reduced. Therefore, the Mn content is set to 1.00% or less, preferably 0.50% or less. On the other hand, the lower limit of the Mn content is not particularly limited. From the viewpoint of obtaining the above-mentioned effects brought about by Mn, the Mn content is preferably 0.05% or more, and more preferably 0.08% or more.
[0033] <P: 0.050% or less>
[0034] P is an element that may reduce the toughness of stainless steel. Therefore, the P content is set to 0.050% or less, preferably 0.040% or less. On the other hand, there is no particular lower limit for the P content, but the lower the P content, the more time is required for the refining process, and the manufacturing cost may increase. Therefore, the P content is preferably 0.001% or more, and more preferably 0.010% or more.
[0035] <S: 0.0030% or less>
[0036] S is an element that generates sulfide-based inclusions and may reduce the power generation efficiency of SOFCs due to evaporation and poisoning of the electrode. Therefore, the S content is set to 0.0030% or less, preferably 0.0015% or less. On the other hand, the lower limit of the S content is not particularly limited. However, the lower the S content, the more time is required for the refining process, and the manufacturing cost may increase. Therefore, the S content is preferably 0.0001% or more, more preferably 0.0002% or more.
[0037] <Cr: 13.0% or more and less than 22.0%>
[0038] Cr is a main element used to form a passive film on the surface of stainless steel materials, and can improve properties such as corrosion resistance and heat resistance through the passive film. From the viewpoint of forming a Cr oxide film with excellent conductivity at temperatures below 600°C, the Cr content is set to 13.0% or more, preferably 13.5% or more. On the other hand, if the Cr content is too high, the toughness and thermal shock resistance will decrease. Therefore, the Cr content is less than 22.0%, preferably 21.0% or less.
[0039] <Mo: 1.50% or less>
[0040] Mo is a main element used to strengthen the passive film of stainless steel materials, and can improve properties such as corrosion resistance and heat resistance through the passive film. In addition, Mo is also an element that promotes the formation of a Cr oxide film on stainless steel materials at temperatures below 600°C and improves conductivity. Usually, the Cr oxide formed at temperatures below 600°C contains Fe, so the conductivity is low. However, by making Mo present in the Cr oxide, the conductivity can be improved. However, if the Mo content is too high, the toughness and thermal shock resistance may decrease due to hardening. Therefore, the Mo content is set to 1.50% or less, preferably 1.30% or less, more preferably 1.00% or less. On the other hand, the lower limit of the Mo content is not particularly limited. From the viewpoint of obtaining the above effects brought by Mo, the Mo content is preferably 0.05% or more, more preferably 0.30% or more.
[0041] <N: 0.030% or less>
[0042] N is an element that combines with Al to form AlN, which is the starting point of abnormal oxidation and may reduce the toughness of stainless steel materials. Therefore, the N content is set to 0.030% or less, preferably 0.025% or less. On the other hand, the lower limit of the N content is not particularly limited. However, the lower the N content, the more time is required for the refining process, and the manufacturing cost may increase. Therefore, the N content is preferably 0.001% or more, more preferably 0.010% or more.
[0043] <Al: 0.30% or less>
[0044] Al is an element that promotes the formation of Cr oxide film of stainless steel at a temperature below 600°C, thereby effectively improving the conductivity. However, if the Al content is too much, it becomes easy to generate AlN, which becomes the starting point of abnormal oxidation, and the toughness and heat shock resistance of the stainless steel may be reduced. Therefore, the Al content is set to 0.30% or less, preferably 0.25% or less. On the other hand, the lower limit of the Al content is not particularly limited. From the viewpoint of obtaining the above-mentioned effect brought about by Al, the Al content is preferably 0.01% or more, and more preferably 0.03% or more.
[0045] <Nb: 0.40% or less>
[0046] Nb, like Ti, preferentially combines with C and N to form Nb carbonitrides, and is therefore an effective element for the high purification of stainless steel. Therefore, Nb promotes the formation of Cr oxide film at temperatures below 600°C, which helps to improve conductivity. In addition, Nb is also an element that suppresses the reduction in corrosion resistance caused by the formation of Cr carbonitrides. However, if the Nb content is too much, the amount of solid-solution Nb that is not consumed in the formation of Nb carbonitrides increases. As a result, toughness and heat shock resistance may be reduced due to hardening. Therefore, the Nb content is set to less than 0.40%, preferably less than 0.35%. On the other hand, the lower limit of the Nb content is not particularly limited. From the viewpoint of obtaining the above-mentioned effects brought about by Nb, the Nb content is preferably more than 0.01%, and more preferably more than 0.05%.
[0047] <Ti: 0.40% or less>
[0048] Ti, like Nb, preferentially combines with C and N to form Ti carbonitrides, and is therefore an element effective for the high purification of stainless steel. Therefore, Ti promotes the formation of Cr oxide film at temperatures below 600°C, which helps to improve conductivity. In addition, Ti is also an element that suppresses the reduction in corrosion resistance caused by the formation of Cr carbonitrides. However, if the Ti content is too high, the Ti carbonitrides coarsen, which becomes the starting point, and the toughness and heat shock resistance decrease. Therefore, the Ti content is set to less than 0.40%, preferably less than 0.35%. On the other hand, the lower limit of the Ti content is not particularly limited. From the viewpoint of obtaining the above-mentioned effects brought about by Ti, the Ti content is preferably greater than 0.01%, and more preferably greater than 0.05%.
[0049] <Ni: 1.00% or less>
[0050] Ni is an element that improves the corrosion resistance of stainless steel and suppresses the reduction of toughness. However, since Ni is an austenite phase stabilizing element, if the Ni content is too much, the thermal expansion coefficient increases and the thermal shock resistance decreases. Therefore, the Ni content is set to 1.00% or less, preferably 0.80% or less. On the other hand, the lower limit of the Ni content is not particularly limited. From the viewpoint of obtaining the above-mentioned effect brought about by Ni, the Ni content is preferably 0.01% or more, and more preferably 0.05% or more.
[0051] <Cu: 1.00% or less>
[0052] Cu is an element that improves the corrosion resistance and electrical conductivity of stainless steel. However, since Cu is an austenite phase stabilizing element, if the Cu content is too much, the thermal expansion coefficient increases and the thermal shock resistance decreases. Therefore, the Cu content is set to 1.00% or less, preferably 0.80% or less. On the other hand, the lower limit of the Cu content is not particularly limited. From the viewpoint of obtaining the above-mentioned effect brought about by Cu, the Cu content is preferably set to 0.01% or more, and more preferably 0.03% or more.
[0053] <High purity index: less than 1.50%>
[0054] The high purity index is represented by the following formula (1).
[0055] High purity index = 10(C+N)+15S+8P+2(Ti+Nb)…(1)
[0056] In the formula, each element symbol represents the content of each element.
[0057] If the high purity index is too high, the amount of Cr in the surface layer of the stainless steel material is consumed and reduced in the formation of carbonitrides, etc., which impairs the formation of the Cr oxide film at a temperature below 600°C. As a result, while the conductivity is reduced, the surface layer is prone to cracking starting from carbonitrides, resulting in a decrease in thermal shock resistance. Therefore, the high purity index is less than 1.50%, preferably less than 1.30%, and more preferably less than 1.00%. On the other hand, the lower limit of the high purity index is not particularly limited. In order to suppress excessive refining load and the increase in raw material costs, the high purity index is preferably 0.30% or more, and more preferably 0.40% or more.
[0058] <B: 0.0050% or less>
[0059] B is an element that increases the grain boundary strength by preferentially concentrating at the grain boundary, and is effective in improving secondary workability, and is included in stainless steel materials as needed. However, if the B content is excessive, the boride (Cr2B) at the grain boundary coarsens, thereby reducing the heat shock resistance. Therefore, the B content is set to 0.0050% or less, preferably 0.0030% or less. On the other hand, the lower limit of the B content is not particularly limited. From the viewpoint of obtaining the above-mentioned effect brought about by B, the B content is preferably 0.0002% or more, and more preferably 0.0005% or more.
[0060] <Sn: 0.5% or less>
[0061] Sn is an element effective in improving the corrosion resistance and electrical conductivity of stainless steel, and is contained in stainless steel as required. However, if the Sn content is too much, hot workability and toughness will decrease. Therefore, the Sn content is set to 0.5% or less, preferably 0.3% or less. On the other hand, the lower limit of the Sn content is not particularly limited. From the viewpoint of obtaining the above-mentioned effects brought about by Sn, the Sn content is preferably 0.01% or more, and more preferably 0.05% or more.
[0062] <V: 0.5% or less>
[0063] V is an element that improves the strength without damaging the toughness of stainless steel, and is included in stainless steel as needed. However, if the V content is too much, the workability and toughness may be reduced, and the cost will increase. Therefore, the V content is set to 0.5% or less, preferably 0.4% or less. On the other hand, the lower limit of the V content is not particularly limited. From the viewpoint of obtaining the above-mentioned effect brought about by V, the V content is preferably 0.01% or more, and more preferably 0.05% or more.
[0064] <W: 0.5% or less>
[0065] W is an element that improves the strength without damaging the toughness of stainless steel, and is contained in stainless steel as needed. However, if the W content is too high, workability and toughness may be reduced, and the cost will increase. Therefore, the W content is set to 0.5% or less, preferably 0.4% or less. On the other hand, the lower limit of the W content is not particularly limited. From the viewpoint of obtaining the effect brought by W, the W content is preferably 0.01% or more, and more preferably 0.05% or more.
[0066] <Ca: 0.010% or less>
[0067] Ca is an element that fixes S and is effective for the high purity of stainless steel, and is contained in stainless steel as needed. However, if the Ca content is too much, the amount of inclusions generated increases, which reduces the conductivity and heat shock resistance. Therefore, the Ca content is set to 0.010% or less, preferably 0.005% or less. On the other hand, the lower limit of the Ca content is not particularly limited. From the viewpoint of obtaining the above-mentioned effect brought about by Ca, the Ca content is preferably 0.0005% or more, and more preferably 0.0010% or more.
[0068] <Mg: 0.010% or less>
[0069] Mg is an element effective for refining stainless steel and is contained in stainless steel as required. However, if the Mg content is too high, the amount of inclusions generated increases, which reduces the conductivity and heat shock resistance. Therefore, the Mg content is set to 0.010% or less, preferably 0.005% or less. On the other hand, the lower limit of the Mg content is not particularly limited. From the viewpoint of obtaining the above-mentioned effect brought about by Mg, the Mg content is preferably 0.0001% or more, and more preferably 0.0005% or more.
[0070] <Zr: 0.50% or less>
[0071] Zr is an element that fixes C and is effective for high-purification of stainless steel, and is contained in stainless steel as needed. However, if the Zr content is too high, the workability of the stainless steel is reduced. Therefore, the Zr content is set to 0.50% or less, preferably 0.40% or less. On the other hand, the lower limit of the Zr content is not particularly limited. From the viewpoint of obtaining the above-mentioned effect brought about by Zr, the Zr content is preferably 0.001% or more, and more preferably 0.005% or more.
[0072] <Co: 0.5% or less>
[0073] Co is an element that improves the strength without damaging the toughness of stainless steel, and is included in stainless steel as needed. However, if the Co content is too much, the workability and toughness may be reduced, and the cost will increase. Therefore, the Co content is set to 0.5% or less, preferably 0.4% or less. On the other hand, the lower limit of the Co content is not particularly limited. From the viewpoint of obtaining the above-mentioned effect brought about by Co, the Co content is preferably 0.01% or more, and more preferably 0.05% or more.
[0074] <Ga: 0.01% or less>
[0075] Ga is an element that improves the hot workability of stainless steel and is included in stainless steel as needed. However, if the Ga content is too much, the manufacturability is reduced. Therefore, the Ga content is set to 0.01% or less, preferably 0.005% or less. On the other hand, the lower limit of the Ga content is not particularly limited. From the viewpoint of obtaining the above-mentioned effect brought about by Ga, the Ga content is preferably 0.0001% or more, more preferably 0.0005% or more.
[0076] <Hf: 0.10% or less>
[0077] Hf is an element that fixes C and is effective for high-purification of stainless steel, and is contained in stainless steel as needed. However, if the Hf content is too high, the workability of the stainless steel is reduced. Therefore, the Hf content is set to 0.10% or less, preferably 0.08% or less. On the other hand, the lower limit of the Hf content is not particularly limited. From the viewpoint of obtaining the above-mentioned effect brought about by Hf, the Hf content is preferably 0.001%, and more preferably 0.005%.
[0078] <REM: 0.10% or less>
[0079] REM (rare earth element) preferentially combines with S and P to form a compound, so it is possible to suppress the reduction in conductivity and heat shock resistance caused by S and P. REM is contained in stainless steel as needed. However, if the REM content is too much, the stainless steel will harden, and the toughness and processability may be reduced. Therefore, the REM content is set to less than 0.10%, preferably less than 0.08%. On the other hand, the lower limit of the REM content is not particularly limited. From the viewpoint of obtaining the above-mentioned effects brought about by REM, the REM content is preferably 0.001% or more, and more preferably 0.005% or more.
[0080] Furthermore, REM is a general term for two elements, scandium (Sc) and yttrium (Y), and 15 elements (lanthanoids) from lanthanum (La) to lutetium (Lu). They can be used alone or in the form of a mixture. Among REM, La and Y are preferred.
[0081] In the stainless steel material according to the embodiment of the present invention, the crystal orientation ratio ({200} / [{110}+{211}]) of the crystal orientation {200} to the total of the crystal orientations {110} and {211} at a depth of 10 μm from the surface is preferably less than 0.30, more preferably 0.25 or less. The lower limit of the crystal orientation ratio is not particularly limited, but is preferably 0.05 or more, more preferably 0.10 or more.
[0082] The reduction in the heat shock resistance of stainless steel is caused by the difference between the texture of the surface layer of the stainless steel and the texture of the parent phase of the stainless steel, which makes the surface layer prone to cracking. In particular, when there are many crystal orientations {200} with low plastic deformation ability in the surface layer of the stainless steel, cracking becomes easy to occur. Therefore, by controlling the crystal orientation ratio ({200} / [{110}+{211}]) to less than 0.30, the ratio of the crystal orientation {200} that becomes the starting point of cracking is reduced, and the occurrence of cracking is suppressed, thereby improving the heat shock resistance.
[0083] In addition, the conductivity of stainless steel at a temperature below 600°C depends on the increase in the Cr concentration of the Cr oxide film ((Cr, Fe)2O3) generated on the surface of the stainless steel. However, by controlling the crystal orientation ratio ({200} / [{110}+{211}]) to less than 0.30, the orientation of the Cr oxide film is improved, and the Cr concentration of the surface layer ((Cr, Fe)2O3) can be increased, thereby improving the conductivity at a temperature below 600°C.
[0084] Here, in this specification, the crystal orientation is obtained by X-ray diffraction of the surface of the stainless steel material. Specifically, the stainless steel material is cut, and the crystal orientation is measured on its surface using an X-ray diffraction device (RINT 2500 manufactured by Rigaku Co., Ltd.). For example, a copper tube ball is used, and the characteristic X-rays of CuKα (wavelength (λ) = 1.5444 angstroms) emitted therefrom are used for diffraction. In this case, in the 2θ method, {110} is detected at 44.79°, {200} is detected at 65.20°, and {211} is detected at 82.58°, so the X-ray intensity ratio of these crystal planes is calculated.
[0085] The stainless steel material according to the embodiment of the present invention preferably has a ratio of the crystal orientation {111}±15° at the center of the thickness direction (the position of t / 2 when the thickness of the stainless steel material is t) exceeding 60%, more preferably 65% to 99%. The upper limit of the ratio is preferably 98%, more preferably 95%.
[0086] By controlling the crystal orientation at the center of the thickness direction as described above, it becomes difficult for the surface layer to crack, thereby improving the thermal shock resistance. In addition, by controlling the crystal orientation as described above, it becomes easy to make the surface oxide film high in Cr, thereby improving the thermal shock resistance and the electrical conductivity at a temperature below 600°C.
[0087] Here, in this specification, the ratio of the crystal orientation {111} ± 15° can be measured using an EBSP orientation analysis system that can visualize the crystal orientation of each grain. Specifically, the stainless steel material is cut, ground (thinning) to t / 2 from its surface, and its surface is ground by colloidal silica to remove the processing strain, and EBSP orientation analysis is performed. For example, in the orientation analysis, it is preferred to include an area of 1 mm width and 2 mm length. The ratio of {111} ± 15° is obtained by dividing it into an area of {111} ± 15° and an area consisting of orientations other than it in the crystal orientation mapping representation of the EBSP orientation analysis system.
[0088] The shape of the stainless steel material according to the embodiment of the present invention is not particularly limited, but is preferably in the form of a plate or foil. When the stainless steel material is in the form of a plate or foil, its thickness is, for example, 0.1 to 5.0 mm, preferably 0.1 to 3.0 mm, more preferably 0.1 to 1.0 mm, and further preferably 0.1 to 0.5 mm.
[0089] The stainless steel material according to the embodiment of the present invention can be produced by a known method except that a slab having the above-mentioned composition is used.
[0090] Here, an example of a typical method for producing a stainless steel material according to an embodiment of the present invention will be described. In addition, the method for producing a stainless steel material according to an embodiment of the present invention is not limited to the following method.
[0091] The stainless steel material according to the embodiment of the present invention can be produced by hot rolling a steel billet having the above-mentioned composition and then cold rolling the steel billet. The conditions for hot rolling and cold rolling are not particularly limited and may be appropriately adjusted according to the composition.
[0092] Cold rolling after hot rolling may include intermediate rolling and finish rolling. Intermediate rolling is preferably performed using a large diameter roller having a diameter of 100 mm or more. By using such a large diameter roller for intermediate rolling, strain can be easily introduced near the center of the plate thickness in addition to the surface layer, so it becomes easy to control the crystal orientation as described above. Finish rolling is preferably performed using a small diameter roller.
[0093] In the case of stainless steel which is harder than carbon steel, cold rolling is generally performed using a multi-pass small-diameter roll such as a Sendzimir multi-roll mill. Cold rolling using large-diameter rolls can be performed using a tandem mill used for cold rolling of carbon steel, for example.
[0094] The cold-rolled material obtained by cold rolling is preferably subjected to surface grinding after pickling. By setting such conditions, it becomes easy to control the crystal orientation of the stainless steel material within the above-mentioned range.
[0095] The method of surface grinding is not particularly limited, and for example, buffing grinding, grindstone grinding, etc. can be used. The thickness of the surface grinding is not particularly limited, but can be 0.001 to 0.050 mm.
[0096] After hot rolling, known steps such as annealing and pickling may be performed.
[0097] The stainless steel material according to the embodiment of the present invention manufactured as described above forms a passive film on the surface in an oxygen-containing atmosphere (e.g., air atmosphere). The passive film has excellent conductivity at a temperature below 600°C. In addition, since the stainless steel material has excellent thermal shock resistance, it is suitable for use in solid oxide fuel cells, especially low-temperature solid oxide fuel cells that operate in a temperature range below 600°C (e.g., 500 to 600°C).
[0098] When the stainless steel material according to the embodiment of the present invention is used in a solid oxide fuel cell, the stainless steel material can be used for components such as separators, current collectors (e.g., air electrode current collectors and fuel electrode current collectors), interconnectors, bus bars, end plates, fuel electrode frames, etc. Among these components, the stainless steel material according to the embodiment of the present invention is preferably used for one or more components selected from separators, interconnectors, and current collectors.
[0099] A solid oxide fuel cell member according to an embodiment of the present invention includes a stainless steel material according to an embodiment of the present invention. In addition, a solid oxide fuel cell according to an embodiment of the present invention includes a solid oxide fuel cell member according to an embodiment of the present invention.
[0100] The solid oxide fuel cell member is not particularly limited, and examples thereof include the various members described above.
[0101] The stainless steel material can be appropriately processed in shape according to the shapes of various components. In addition, a conductive coating can also be formed on the surface of the stainless steel material. The conductive coating is not particularly limited and can be formed from materials known in the technical field. For example, the conductive coating can be formed using metals with excellent conductivity such as Ag and Co. In addition, the conductive coating can be a layer of a single metal or a layer of an alloy, and can be a single-layer structure or a stacked structure.
[0102] Furthermore, from the viewpoint of improving the adhesion with the conductive coating, the stainless steel material may also be subjected to modification (roughening) of the passive film. For example, modification (roughening) of the passive film may be performed by a known method such as immersing the stainless steel material in a fluorine-nitric acid solution.
[0103] Example
[0104] The present invention will be described in detail below with reference to examples, but the present invention should not be construed as being limited to these examples.
[0105] The slabs of the composition shown in Table 1 were melted, heated to 1200°C, and then hot rolled to produce hot rolled plates with a thickness of 3.0 mm. Then, the hot rolled plates were annealed and pickled, and then cold rolled. In the cold rolling, the hot rolled plates were intermediately rolled at 40 to 60% using a large diameter roll with a diameter of 100 mm, intermediate annealing and pickling were performed, and then finish rolled using a small diameter roll to produce a cold rolled plate with a thickness of 0.1 to 0.5 mm. Thereafter, the cold rolled plates were finally annealed and pickled, and the surface was ground by grinding stones to 0.005 to 0.01 mm, thereby obtaining stainless steel materials. In addition, stainless steel materials obtained by cold rolling using the same small diameter rolls as those used for finish rolling were also manufactured. The roll diameters used in the intermediate rolling are shown in Table 2.
[0106] Table 1
[0107]
[0108] Next, for the obtained stainless steel material, the crystal orientations {110}, {211}, and {200} at a depth of 10 μm from the surface were measured, and the crystal orientation ratio ({200} / [{110}+{211}]) was obtained. In addition, the ratio of the crystal orientation {111}±15° at the center of the thickness direction was measured. The crystal orientation was measured under the above conditions. The results are shown in Table 2.
[0109] The electrical conductivity and thermal shock resistance of the obtained stainless steel material were evaluated in the following manner.
[0110] (1) Electrical conductivity
[0111] The stainless steel material was immersed in an aqueous solution (liquid temperature 60° C.) containing 5.0 mass % hydrofluoric acid and 15 mass % nitric acid for 1 to 5 minutes to perform surface modification, and then subjected to coating treatment to form a conductive coating. During the coating treatment, adjustment was made so that a Co plating layer was formed on the surface of the surface-modified stainless steel material with a thickness of 2 to 5 μm.
[0112] Two pieces of stainless steel material with conductive coating (hereinafter referred to as "conductively coated stainless steel material") were exposed to heat at 600°C for 1000 hours in a dry air atmosphere adjusted to a dew point of -40°C (H2O concentration: about 0.013%), and then used to prepare the following Figure 1 The test piece for measurement shown above was measured by a four-terminal method using a potentiostat. Specifically, the measurement was performed as follows.
[0113] First, a conductive paste (Ag paste) was applied to the center of two sheets of stainless steel materials 10 with conductive coating in a square shape (10 mm on one side, 10 μm thick), and dried to form a conductive portion 20. Next, the conductive portions 20 of the two sheets of stainless steel materials 10 with conductive coating were overlapped and arranged in a cross shape, and then sandwiched between alumina plates, a weight (200 g) was placed, and the conductive portion 20 was sintered in an electric furnace (850°C × 30 minutes). Next, a small cutter was used to cut the surface until the metal base material was exposed, forming a conductive portion 20. Figure 1 Next, the silver wire 40 It is wound around the wiring installation part 30, coated with conductive paste, and dried at 150°C for 30 minutes to obtain a test piece for measurement. Next, the test piece for measurement is placed in a high-temperature electrochemical measurement device, and the voltage-current curve is obtained by a four-terminal method using a constant potential meter. In this measurement, the measurement temperature is set to 600°C, and the voltage is scanned until 10mV. In addition, the resistance value is calculated from the slope of the voltage-current curve. In this evaluation, the resistance value is set to 20mΩ·cm 2 The following cases were judged as A (particularly excellent high temperature conductivity), and the resistance value exceeded 20 mΩ·cm 2 and 50mΩ·cm 2 The following cases were judged as B (excellent high temperature conductivity), and the resistance value exceeded 50 mΩ·cm 2 The case was judged as C (insufficient high temperature conductivity).
[0114] (2) Thermal shock resistance
[0115] The heat shock resistance was evaluated by repeatedly heating and cooling the above-mentioned stainless steel material with a conductive coating. Specifically, the above-mentioned stainless steel material with a Co plating and a conductive coating was cut to prepare a 10mm×25mm test piece. Then, the test piece was placed in a mobile muffle furnace heated to 600°C and kept in the atmosphere (in the muffle furnace) for 25 minutes, released from the atmosphere and cooled for 5 minutes (muffle furnace movement). The above process was regarded as 1 cycle, and 100 cycles of intermittent heating tests were performed. In the intermittent heating test, the case where the Co plating did not peel off was judged as A (high heat shock resistance), and the case where the Co plating peeled off was judged as C (low heat shock resistance).
[0116] Table 2 shows the above-mentioned evaluation results.
[0117] Table 2
[0118]
[0119] As shown in Table 2, the stainless steel materials of Test Nos. 1 to 13 (Examples of the present invention) have excellent electrical conductivity and thermal shock resistance because they have the prescribed composition. In particular, the stainless steel materials of Test Nos. 2, 4, 9, and 13 have the preferred composition and are subjected to intermediate rolling (cold rolling) using large-diameter rolls, so that the crystal orientation is within the preferred range and the electrical conductivity is very good.
[0120] In contrast, the stainless steel materials of Test No. 14 to 20 (Comparative Examples) have insufficient electrical conductivity or thermal shock resistance because their compositions or high purity indexes are outside the prescribed range. In particular, Test No. 16 and 18 to 20 have appropriate crystal orientations by implementing intermediate rolling (cold rolling) using large-diameter rolls, but the amounts of Cr, Mo, or Al are outside the prescribed range. Therefore, Test No. 16 has insufficient electrical conductivity, and Test No. 18 to 20 have insufficient thermal shock resistance.
[0121] As can be seen from the above results, according to the present invention, a stainless steel material for solid oxide fuel cells having excellent electrical conductivity and thermal shock resistance at a temperature of 600° C. or less and a method for manufacturing the same can be provided. In addition, according to the present invention, a solid oxide fuel cell member and a solid oxide fuel cell having the stainless steel material for solid oxide fuel cells having such characteristics can be provided.
[0122] Description of Reference Numerals
[0123] 10 Stainless steel with conductive coating
[0124] 20 Conductive part
[0125] 30 Wiring installation department
[0126] 40 Silver Wire
Claims
1. A stainless steel material for a solid oxide fuel cell, comprising, by mass, C: 0.030% or less, Si: 1.00% or less, Mn: 1.00% or less, P: 0.050% or less, S: 0.0030% or less, Cr: 13.0% or more and less than 22.0%, Mo: 1.50% or less, N: 0.030% or less, Al: 0.30% or less, Nb: 0.40% or less, Ti: 0.40% or less, Ni: 1.00% or less, Cu: 1.00% or less, a high purity index represented by the following formula (1) being less than 1.50%, and the balance being Fe and impurities, At a depth of 10 μm from the surface, the crystal orientation ratio of {200} to the total of the crystal orientations {110} and {211}, that is, {200} / [{110}+{211}], is less than 0.
30. High purity index = 10(C+N)+15S+8P+2(Ti+Nb)···(1) In the formula, each element symbol represents the content of each element.
2. The stainless steel material for solid oxide fuel cells according to claim 1, further comprising, by mass, one or more selected from the group consisting of B: 0.0050% or less, Sn: 0.5% or less, V: 0.5% or less, W: 0.5% or less, Ca: 0.010% or less, Mg: 0.010% or less, Zr: 0.50% or less, Co: 0.5% or less, Ga: 0.01% or less, Hf: 0.10% or less, and REM: 0.10% or less.
3. The stainless steel material for a solid oxide fuel cell according to claim 1 or 2, wherein the ratio of the crystal orientation {111}±15° at the center in the thickness direction exceeds 60%.
4. The stainless steel material for a solid oxide fuel cell according to claim 1 or 2, which is used for one or more members selected from the group consisting of a separator, an interconnector, and a current collector.
5. A method for producing a stainless steel material for a solid oxide fuel cell, comprising hot rolling a slab and then cold rolling the slab, wherein the slab comprises, by mass, C: 0.030% or less, Si: 1.00% or less, Mn: 1.00% or less, P: 0.050% or less, S: 0.0030% or less, Cr: 13.0% or more and less than 22.0%, Mo: 1.50% or less, N: 0.030% or less, Al: 0.30% or less, Nb: 0.40% or less, Ti: 0.40% or less, Ni: 1.00% or less, Cu: 1.00% or less, a high purity index represented by the following formula (1) is less than 1.50%, and the balance is Fe and impurities, The cold rolling includes the step of performing intermediate rolling using a large-diameter roll having a diameter of 100 mm or more. High purity index = 10(C+N)+15S+8P+2(Ti+Nb)···(1) In the formula, each element symbol represents the content of each element.
6. The method for manufacturing a stainless steel material for a solid oxide fuel cell according to claim 5, wherein the slab further comprises, by mass, one or more selected from the group consisting of B: 0.0050% or less, Sn: 0.5% or less, V: 0.5% or less, W: 0.5% or less, Ca: 0.010% or less, Mg: 0.010% or less, Zr: 0.50% or less, Co: 0.5% or less, Ga: 0.01% or less, Hf: 0.10% or less, and REM: 0.10% or less.
7. The method for producing a stainless steel material for a solid oxide fuel cell according to claim 5 or 6, wherein the cold-rolled material obtained by the cold rolling is pickled and then surface-ground. 8 . A member for a solid oxide fuel cell, comprising the stainless steel material for a solid oxide fuel cell according to claim 1 . 9 . A solid oxide fuel cell comprising the solid oxide fuel cell member according to claim 8 .
Citation Information
Patent Citations
Fuel cell system and operation method therefor and electrochemical system
JP2020053388A
Ferritic stainless steel sheet and method for producing ferritic stainless steel sheet with oxide coating film having excellent conductivity and adhesion
CN104379790A
Ferritic stainless steel, steel sheet thereof, and methods for producing these
CN109196133A
Ferritic stainless steel for solid oxide type fuel cell excellent in heat resistance and production method therefor
JP2017125248A